Fabrication and Characterization of a Novel Eco-Friendly Plant Microbial Soil Cell - V, Nirbhay; Singh, Monika (International Journal of Computer Sciences and Engineering, 2020)
In present study our attempt is to generate electric power from plant and soil. We fabricated microbiological soil cell by using different plantand soil samples (Laterite, Red Alluvial and saline soil). Certain amount of soil sample diluted with water which act as electrolyte and Copper and Zinc plate use as positive and negative electrode respectively. Maximum value of 0.9 Volt has been obtain from cell having saline soil. Water hyacinth and gametophyte plant grown in the soilto construct plant microbiological soil cell.The plant soil cell so constructed are found to providestable voltage of about 1.5 volt per cellfor time of about one month. The cell so constructed is pollution free, eco-friendly and found to be rechargeable by adding specific quantity of water. The working model based on this research is also selected for National Level Science exhibition.